Green practice: an empirical investigation on the interiors of healthy restaurants in Penang / Shi Ying Chua and Muhammad Firzan Abdul Aziz - Shi, Ying Chua; Abdul Aziz, Muhammad Firzan (UiTM Press, 2024)
Green practices are typically categorised into four (4) areas: food and beverage, service, management, and the environment. The implementation of green practices, particularly those emphasising green interior design, however, is still in its infancy state and remains scarce. This study delves into the realm of green practices within the context of healthy restaurants, with two (2) primary objectives. First, to understand the interior design rationale of healthy restaurants in Penang, and second, to explore the perception of restaurateurs regarding the implementation of green practices for the interiors of their respective healthy restaurant. To gather primary data, the study conducted semi-structured, key informant interviews with restaurateurs in Penang, Malaysia, who met specific criteria which include the adoption of food-focused green practices, the presence of aesthetically pleasing interior designs, and the given positive reviews for both food quality and restaurant ambiance. The findings revealed that these restaurant owners effectively conveyed their concepts through their interior designs, using natural materials like wood, cement, and indoor plants. While they demonstrated awareness of environmental sustainability and health concerns, their understanding of green practices was somewhat basic. They were more focused on applying green practices to food and beverages than on creating a green interior ambiance.